Reformasi Pendidikan Global: Membangun Sistem Pendidikan yang Responsif terhadap Perubahan Sosial dan Teknologi: Global Education Reform: Building Education Systems Responsive to Social and Technological Change - Rosdiana Rosdiana; Fitriani Yuniar; Dewi Agustina Solihin; Aam Amaliah; Syamsul Anwar (ITScience (Information Technology and Science), 2024)
Rapid social change and technological developments require global education systems to transform to remain relevant and effective. This study aims to examine how education reform can be realized through adaptive curriculum, utilization of technology, and strengthening the role of teachers. Using a qualitative approach through literature studies and comparative analysis, this study analyzes various models of education reform from several countries, such as Finland, Singapore, South Korea, Estonia, the Netherlands, and Australia. The results show that a competency-based adaptive curriculum provides flexibility in learning, allowing students to develop 21st-century skills, including digital literacy, critical thinking, and adaptability. The integration of technology, such as artificial intelligence and digital platforms, supports personal and collaborative learning, although its implementation is still hampered by infrastructure in many developing countries. In addition, strengthening teacher capacity through continuous training is key to the success of reform, ensuring that teachers are able to adopt technology and innovative teaching methods. This study offers a holistic framework for global education reform, combining technology, flexible policies, and teacher professional development. The novelty of this study lies in the comprehensive approach that does not only focus on one aspect but rather the integration of the three elements to create an education system that is responsive to social and technological change. The practical recommendations produced will support policymakers and educational institutions in implementing sustainable and inclusive reforms.